The Impact of Nucleos(t)ide Analogs Off-Therapy Among Chronic Hepatitis B Patients: A Systematic Review and Meta-Analysis - Chen, Ping; Qian, Mingxia; Fu, Rongrong; Shen, Xinlan; Yue, Dengyuan; Wang, Ning; Gu, Lihu (Frontiers in Public Health, 2021)
Background and Aim: Although most chronic hepatitis B (CHB) patients achieve effective virological suppression after receiving long-term nucleos(t)ide analogues (Nucs) therapy, the safety of off-therapy is controversial under the monitor. Methods: We identified studies through searching PubMed, Embase, Cochrane Library, and Web of Science from January 1990 to February 2021. The eligible studies compare the long outcomes between discontinued and continued Nucs treatments groups among CHB patients. This study was conducted to investigate long-term outcomes, including biochemical, serological, and virological outcomes, as well as hepatocellular carcinoma (HCC) development rate between discontinued and maintained Nucs therapy groups among CHB patients. Results: Five eligible studies covering 1425 patients were selected for meta-analysis. Our result exhibits that patients with Nucs off-treatment have a higher risk of alanine aminotransferase (ALT) flares-up than those who continued Nucs therapy under the monitor (OR=9.39, 95%CI=3.87-22.78). Nucs off-therapy patients have a higher virological bound incidence (OR=617.96, 95%CI=112.48-3395.14) and a higher HBV DNA level (OR=9.39, 95%CI=3.87-22.78) than those who continued Nucs therapy. There was no statistically significant difference in the risk of hyperbilirubinaemia, hepatic decompensation, and HCC development between both two groups. Patients in Nucs off-therapy group demonstrate a higher HBsAg loss rate than those in the continued group (OR=7.10, 95%CI=6.68-13.69). Conclusions: Nucs off-therapy patients may exhibit a higher chance of achieving HBsAg loss than those who continue Nucs therapy. It requires close monitoring after Nucs off-therapy and timely restarting of Nucs therapy when ALT concentrations increase.